A questão da inexauribilidade do texto: o Frühromantik e a escritura derridiana - Guidotti, Mirella [UNESP]; Maas, Wilma Patricia Marzari Dinardo [UNESP] (My University, 2011)
This article aims to investigate the configuration on the new scenario, during the Early German Romanticism, which led to dismantle the philosophical discourse as the expression of a safe and fixed content, free from the ambiguity of figural language. Our main argument is that already Schelling’s concept of symbol brings up the question about the opacity of the text. By analyzing to what extent this problematization around the language lingers on in the contemporariness, we refer to Derrida’s thought which points out to the illusion embedded in the pretension to conceive a clear and unambiguous language, creating therefore a new ground between art and philosophy since the text itself as a neutral and closed subject will be questioned now.

A partir das concepções estéticas dos Românticos de Jena, apontamos para a configuração do novo cenário crítico que desaloja o discurso filosófico como expressão de um conteúdo seguro, fixo e livre das ambiguidades da linguagem figural. Nossa hipótese é a de que, já no conceito de símbolo schellinguiano ocorre a problematização em torno da opacidade do texto. Abordando ainda em que medida esta problematização em torno da linguagem perdura na contemporaneidade, aludimos ao pensamento de Derrida, que aponta para a ilusão contida na pretensão de formular uma linguagem depurada, inequívoca e sem ambiguidades, criando assim um novo espaço na relação entre arte e filosofia, uma vez que agora, o próprio texto enquanto entidade neutra e fechada será questionado.
Keywords: Frühromantik; Symbol; Poetic language; Philosophical language; Derrida’s écriture; Frühromantik; Símbolo; Linguagem poética; Linguagem filosófica; Escritura derridiana